O direito fundamental à razoável duração do processo civil: instrumentalização e efetividade - Varella, Luiz Henrique Borges (2011)
The slowness of the judiciary is a concern of many of those dealing with procedural knowledge. A concern that is probably universal, since many countries consider the length of proceedings with a fundamental problem. In Brazil, the reasonable duration of proceedings was elevated to a fundamental right to Constitutional Amendment n. 45. However, the issue of the amendment was not enough to turn the constitution text into reality. Therefore, some questions arise: how to identify the reasonable length of proceedings? How to effectively implement it? If, on a case, the right to reasonable length of time the process is violated, how to bypass the injury to that right? These are essentially the questions that guided this research, which was founded mainly on the method of literature review, without, however, neglecting the documental research through analysis of national case law and in particular the European Court of Human Rights. To achieve the proposed objectives, initially faced up the problem of interpretation and application of law, concluding that the current stage of legal interpretation, with estates in neoconstitutionalism revolutionized the methodology of law. The enforcement of fundamental rights, then, is the point of departure and arrival in the interpretation and application of the law. On identification of reasonable duration of process, which is essentially an indeterminate legal concept, it was found that there are various criteria for their measurement. The most widely used are those recommended by the European Court of Human Rights, whose jurisprudence reflected in several jurisdictions, including the Brazilian. Finally, with regard to the realization of the fundamental right to reasonable duration of process, it was observed that its effects will radiate in all sectors of government (Executive, Legislative and Judiciary), imposing the conduct of state representatives (but not only them) which, if disregarded, subject to judicial review - by writs, for example - and also administrative - which was strengthened with the creation of the National Council of Justice. In conclusion, then, the reasonable duration of the process will only be achieved with the change of various paradigms, which are mainly for the implementation of an efficient judicial management. It is a summation of forces necessary to make art. 5 °, inc. LXXVIII of the Constitution a reality. It must, therefore, and most of all, a change of culture.